The European Union and the Arctic region. Communication from the Commission to the European Parliament and the Council. - European Commission, -
The European Union is inextricably linked to the Arctic region (hereafter referred to as the Arctic) by a unique combination of history, geography, economy and scientific achievements. Three Member States — Denmark (Greenland), Finland and Sweden — have territories in the Arctic. Two other Arctic states — Iceland and Norway — are members of the European Economic Area. Canada, Russia and the United States are strategic partners of the EU. European Arctic areas are a priority in the Northern Dimension policy[3]. Beyond areas of national jurisdiction, the Arctic Ocean contains parts pertaining to the high seas and the seabed managed by the International Seabed Authority.